Preconditioning by isoflurane as a volatile anesthetic in elective coronary artery bypass surgery - Kiani, Amjad (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2013)
BACKGROUND: Some pharmacological preconditioning approaches are utilized as an effective adjunct to myocardial protection, particularly following cardiac procedures. The current study addressed the potential clinical implications and protective effects of isoflurane as an anesthetic most applicable on postoperative myocardial function measured by cardiac biomarkers. METHODS: 46 patients were included in the study. In 23 of them, preconditioning was elicited after the onset of cardiopulmonary bypass via a 5-minute exposure to isoflurane (2.5 minimum alveolar concentration), followed by a 10-minute washout before aortic cross clamping and cardioplegic arrest. 23 case-matched control patients underwent an equivalent period (15 minutes) of pre-arrest isoflurane-free bypass. Outcome measurements included creatine phosphokinase (CPK) and creatine kinase-MB (CK-MB) levels until 24 hours after the surgery. RESULTS: None of the differences in enzyme levels at baseline and 24 hours after surgery between the two groups reached the threshold of statistical significance. The level of CPK was significantly reduced 24 hours after surgery compared with the baseline in the two groups. However, the postoperative release of CPK was consistently smaller in the isoflurane-preconditioned group than in the control group. The release of CK-MB displayed a statistically similar pattern. Multivariate linear regression analysis showed the effect of isoflurane regimen on reducing CPK level within the 24 hours after surgery compared with placebo. CONCLUSION: Our study supports the cardio protective effect of isoflurane and the role of pharmacological preconditioning of the human heart by this volatile anesthetic during elective coronary artery bypass surgery.